Chytridiomycosis risk among Central European amphibians based on surveillance data - Balá, Vojtech; Vojar, Jirří; Civi, Petr; Andera, Martin; Rozínek, Roman (Diseases of aquatic organisms, 2014)
The Czech Republic hosts a surprisingly rich biodiversity of amphibians representing the majority of amphibian species present in all of Central and Eastern Europe. Surveillance data of Batrachochytrium dendrobatidis (Bd) collected during 2008 to 2012 were analysed for basic patterns of prevalence and infection intensity among species, age groups and localities. In addition, an investigation was made into possible data bias due to varying PCR inhibition. Infection prevalence in the genus Pelophylax was significantly higher than in other sampled taxa, while Bombina and Bufo were infected with intermediate prevalence. Individual mortalities putatively caused by chytridiomycosis were detected in Bombina and Bufo, but not in Pelophylax. Differences among localities were seen to modulate the pathogen's infection rate and influence overall individual infection intensities. PCR inhibition occurred significantly more often in samples from the genus Pelophylax than in other tested taxa (Bufo bufo, B. viridis, Bombina bombina, Pelobates fuscus and Rana dalmatina). Although we found no completely inhibited samples within the genus Bombina, the infection loads were lower in the sample set processed without bovine serum albumin, suggesting some level of PCR inhibition. The combination of high Bd prevalence with no apparent deleterious effect and the high dispersal abilities of water frogs predispose them to act as vectors for chytridiomycosis. It is possible that the role of Pelophylax frogs in the spread of Bd is overlooked due to a large proportion of unrecognized false negatives, but this issue needs further confirmation.
Keywords: Time; mykózy; Animals; čas; Česká republika; Mycoses; Amphibians; Chytridiomycota; zvířata; obojživelníci; Czech Republic